2018
DOI: 10.1111/plb.12877
|View full text |Cite
|
Sign up to set email alerts
|

The role of phenotypic plasticity and pollination environment in the cleistogamous, mixed mating breeding system of Triodanis perfoliata

Abstract: The role of variable pollination environments in maintaining mixed mating systems is an active area of research. Dimorphic cleistogamy, in which a plant reproduces by both open, facultative outcrossing chasmogamous (CH) flowers and closed, cleistogamous (CL) flowers presents an excellent opportunity to study mixed mating. For example, plastic responses in allocation to an optimal floral type could serve as an adaptive strategy that maintains mixed mating under variable pollination environments. We tested for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…Ecological studies at different spatial and temporal scales can detect different components of the genetic or plastic basis of traits such as cleistogamy. Our results expand upon previous work in Triodanis which used greenhouse experiments to examine how differences in soil and light conditions influence reproductive allocation (Colbert 2015), and a field study which examined the role of pollination in the plasticity of cleistogamy (Ansaldi et al 2018). Colbert (2015) found that light increased the proportion of CH flowers, but soil did not influence reproductive plasticity.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Ecological studies at different spatial and temporal scales can detect different components of the genetic or plastic basis of traits such as cleistogamy. Our results expand upon previous work in Triodanis which used greenhouse experiments to examine how differences in soil and light conditions influence reproductive allocation (Colbert 2015), and a field study which examined the role of pollination in the plasticity of cleistogamy (Ansaldi et al 2018). Colbert (2015) found that light increased the proportion of CH flowers, but soil did not influence reproductive plasticity.…”
Section: Discussionsupporting
confidence: 71%
“…Drawing general conclusions about the role of abiotic parameters in trait variation across CL species can be problematic. For example, soil moisture can interact with other factors that influence cleistogamy, such as pollination (Albert et al 2011; Munguía-Rosas et al 2012; Ansaldi et al 2018). Additionally, the strength of response is likely to vary with plant life history, with annuals experiencing stronger selection than perennials on traits that maximize reproduction (Jasieniuk and Lechowicz 1987).…”
Section: Discussionmentioning
confidence: 99%
“…But the extent to which CL flower and fruit production are relatively less costly, as well as the value of CL flowers in providing reproductive assurance will vary with species. In T. perfoliata, CH reproduction is not pollen limited, and CL fruits produce only 10-50% the seeds of CH fruits, depending on pollination conditions, so reproductive assurance via CL flowers may not be as important in this species (Ansaldi et al 2018).…”
Section: Low Inbreeding Depressionmentioning
confidence: 99%
“…Experimental floral manipulations showed that some of the selfing is delayed, and may occur as the stigma curls back towards the style in the later stages of anthesis to make contact with self-pollen present on the style (Goodwillie et al 2018). However, pollination studies in both field and greenhouse indicate that autonomous selfing results in only about 60% as many seeds as flowers that have been supplemented with self-pollen (Ansaldi et al 2018;Goodwillie et al 2018).…”
Section: Low Inbreeding Depressionmentioning
confidence: 99%
See 1 more Smart Citation